Calculating the Sample Size in Quantitative Studies (Scholars' Journal, 2021)
The determination of the required sample size is always an important step during the planning of the quality of research for a quantitative study. The researchers need to have sound prerequisite knowledge of the inferential statistics concept for determining a minimum sample size requirement and its estimation because an insufficient sample size may not be able to answer the research questions and a large sample is wastage of resources, may add to the complexity, and take more time for the study. Both situations are ethically unacceptable for the researchers. Therefore, this study provides researchers with appropriate sample size determination methods for quantitative study. The Google Scholar, PubMed, and Library Genesis were used to find out the required information for the review of this paper. This study presents the sample size calculation formula in a simplified manner with relevant examples so that researchers may effectively use them in their research.